2022
DOI: 10.3390/pharmaceutics14081582
|View full text |Cite
|
Sign up to set email alerts
|

Barium Oxide Doped Magnesium Silicate Nanopowders for Bone Fracture Healing: Preparation, Characterization, Antibacterial and In Vivo Animal Studies

Abstract: Magnesium silicate (MgS) nanopowders doped with barium oxide (BaO) were prepared by sol-gel technique, which were then implanted into a fracture of a tibia bone in rats for studying enhanced in vivo bone regeneration. The produced nanopowders were characterized using X-ray diffraction (XRD), Fourier transform infrared spectra (FTIR), scanning electron microscope with energy-dispersive X-ray spectrometry (SEM-EDX) and transmission electron microscope (TEM). Mechanical and bactericidal properties of the nanopowd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This not only helps patients recover after surgery but also decreases the workload of surgeons and increases the efficiency and quality of care (Liu C et al,2022a). However, traditional biodegradable polymers suffer from insufficient strength and low modulus of elasticity, limiting their application on a large scale (Mabrouk et al,2022). In this regard, the use of biodegradable magnesium-based materials eliminates the issues of stress shielding effect, foreign body reaction, and lack of strength, and their clinical safety and efficacy offer significant advantages over conventional polymer materials (Martin et al,2022).…”
Section: Discussionmentioning
confidence: 99%
“…This not only helps patients recover after surgery but also decreases the workload of surgeons and increases the efficiency and quality of care (Liu C et al,2022a). However, traditional biodegradable polymers suffer from insufficient strength and low modulus of elasticity, limiting their application on a large scale (Mabrouk et al,2022). In this regard, the use of biodegradable magnesium-based materials eliminates the issues of stress shielding effect, foreign body reaction, and lack of strength, and their clinical safety and efficacy offer significant advantages over conventional polymer materials (Martin et al,2022).…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium silicate (MS) is a synthesized silicate that consists of silicon and magnesium. The MS composite has been studied in the eld of bone fracture healing and ligament grafting, and it has shown satisfactory performance [23,24]. Silicon can promote the synthesis of collagen and proteoglycans in bone and cartilage [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant attention has been directed toward the role of barium in bone repair and regeneration, particularly in the context of osteogenesis [24][25][26]. It has been demonstrated that the incorporation of Ba 2+ into bioceramic compositions enhances the mineralization of their surfaces under in vitro conditions, as observed during immersion in simulated body fluid (SBF) [26][27][28][29][30]. One such oxide ceramic mineral phase, which includes silicon, calcium, and barium, is known as walstromite.…”
Section: Introductionmentioning
confidence: 99%